Cardiac complications in diphtheria and predictors of outcomes. (January 2018) - Samdani, Sunil; Jain, Avani; Meena, Vinod; Meena, C.B.
Abstract: Objective: To study the cardiac complications in diphtheria patients and to study the predictors of outcomes. Study Design: Single centre prospective analysis of cardiac complications in diphtheria patients. Results: In this study, there were 60 patients diagnosed with diphtheria with ECG changes. The ECG changes seen were sinus tachycardia (68.3%), T wave inversion (20%), ST segment depression (13.3%), right bundle branch block (5%), multiple atrial ectopics (3.3%). The case fatality rate in our study was 25% (15 patients). High CPK-MB, myoglobulin and cardiac troponin levels were associated with cardiac mortality. In our study, cardiac troponin T had the highest sensitivity (80%) and CK-MB had the highest specificity (95.56%). Conclusion: Cardiac involvement is a common complication of infection with C. diphtheria and is associated with high mortality. As diphtheria can be prevented by adequate vaccination, efforts should be maximized for high vaccine coverage with booster doses.